Kawin Siri Dalam Perspektif Hukum Islam dan Administrasi Kependudukan - Hamid Farihi (SALAM: Jurnal Sosial dan Budaya Syar-i, 2023)
Marriage holds a significant religious significance within the Islamic faith. Nevertheless, the prevalence of unregistered marriages, which lack official documentation, frequently gives rise to legal and administrative predicaments in numerous Muslim nations. Marriages that lack legal recognition by the state can potentially exert significant ramifications on the rights of women and children, while also posing challenges in terms of demographic data management and the provision of public services.  The primary objective of this study is to investigate the viewpoint of Islamic jurisprudence and population governance in relation to unregistered matrimonial unions. This research uses qualitative methods with a literature and legislation approach. Through in-depth analysis of scientific literature, articles and regulations related to unregistered marriage, this research looks for patterns and findings that can support an understanding of these complex issues from the perspective of Islamic law and population administration. The findings of the study shed light on the intricate legal and administrative challenges associated with the management of unregistered marriages. The focal points demanding significant attention are the infringements of the rights of women and children, particularly in relation to their livelihoods, education, and legal safeguards. The primary conclusions of this research pertain to the significance of state-sanctioned acknowledgment of unregistered marriages and the implementation of equitable measures to safeguard individual rights.Keywords: Siri Marriage; Islamic law; Population Administration Abstrak:Pernikahan memiliki makna keagamaan yang signifikan dalam iman Islam. Namun demikian, prevalensi pernikahan yang tidak dicatatkan, yang tidak memiliki dokumentasi resmi, sering kali menimbulkan kesulitan hukum dan administratif di banyak negara Muslim. Perkawinan yang tidak mendapat pengakuan hukum dari negara berpotensi menimbulkan dampak signifikan terhadap hak-hak perempuan dan anak, sekaligus menimbulkan tantangan dalam hal pengelolaan data demografi dan penyediaan layanan publik. Tujuan dari penelitian ini adalah untuk mengetahui sudut pandang yurisprudensi Islam dan tata kelola kependudukan dalam kaitannya dengan perkawinan tidak terdaftar. Penelitian ini menggunakan metode kualitatif dengan pendekatan literatur dan peraturan perundang-undangan. Melalui analisis mendalam terhadap literatur ilmiah, pasal dan peraturan terkait perkawinan tidak dicatatkan, penelitian ini mencari pola dan temuan yang dapat mendukung pemahaman atas permasalahan kompleks tersebut dari perspektif hukum Islam dan administrasi kependudukan. Temuan penelitian ini menyoroti rumitnya tantangan hukum dan administratif yang terkait dengan pengelolaan perkawinan tidak dicatatkan. Hal-hal yang memerlukan perhatian besar adalah pelanggaran terhadap hak-hak perempuan dan anak-anak, khususnya yang berkaitan dengan mata pencaharian, pendidikan, dan perlindungan hukum. Kesimpulan utama dari penelitian ini berkaitan dengan pentingnya pengakuan perkawinan tidak dicatatkan yang direstui negara dan penerapan langkah-langkah yang adil untuk melindungi hak-hak individu.Kata Kunci: Nikah Siri; Hukum Islam; Administrasi Kependudukan